Crystalline Penicillin for Community Acquired Pneumonia: Does it still work? - Aryal, Nirjala; Neopane, Arun Kumar; Thapa, Moon; Singh, Umesh Kumar; Agrawal, Keshav (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Pneumonia is the most common cause of mortality and morbidity in children in underdeveloped countries. The common bacterial agents are Streptococcus pneumonia followed by Haemophilus influenzae type b. The only measure to treat bacterial pneumonia is the correct use of antibiotics along with oxygen in moderate to severe cases. The objectives of this study were to see the clinical features of community-acquired pneumonia and to observe the response to treatment with crystalline penicillin in hospitalized children. Methods: This study was a prospective study. The children aged between two months to 59 months with pneumonia were treated with intravenous crystalline penicillin. Response was observed by normalization of respiratory rate and absence of lower chest indrawing. Results: Out of 88 children treated, 79(89.8%) showed improvement in 48 hours. In children who had tachypnoea, 62.9% showed normalization in respiratory rate in the first 24 hours and 37.1 percent in 48 hours of treatment. Similarly, among children with lower chest indrawing; 61.1% showed improvement in 24hours and the remaining in 48hours. In 24 hours of treatment 17.7% of children became afebrile and 46.8% in 48hours of treatment. Conclusion: The most common clinical features like cough, fever, tachypnoea and lower chest indrawing can be used to diagnose CAP where Chest X- ray is not possible. The response to treatment with Crystalline Penicillin is a very good and, thus, can be used as the first line drug in the treatment of children with CAP. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/36-39 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7908